Patterns of Biomarkers in Cord Blood During Pregnancy and Preeclampsia - Kharb, S.; Nanda, S. (Current Hypertension Reviews, 2017)
Background: Umbilical cord blood (UCB) is in contact with all the fetal tissues and can reflect the state of fetus and UCB can be compared with maternal blood. Inflammatory, metabolic and immunological disorders during pregnancy can affect the environment in which the fetus is developing and may produce various alterations. Objective: To analyze different biochemical parameters in maternal venous blood and new born umbilical cord blood from healthy normotensive pregnant and preeclamptic women. Materials and Methods: Homocysteine, folate, B12, heme oxygenase-1 (HO-1), endoglin, leptin, cholinesterase, IGF-1, Apo A, lipoproteins, TSH, fT3, fT4 were analyzed in maternal sera and venous umbilical cord sera of newborns of twenty five preeclamptics (group II) and twenty five normotensive pregnant women (group I). Homocysteine, folic acid, vitamin B12, Apo A I & II, TSH, fT3, fT4 levels were estimated by competitive immunoassay using direct chemiluminiscence technology. Heme oxygenase-1 (HO-1), endoglin, leptin, cholinesterase, IGF-1 were analyzed by ELISA. Results: Maternal and cord blood levels of homocysteine, folic acid, lipid profile (namely, total cholesterol, triglycerides, LDL-C, VLDL-C and HDL-C), TSH, heme oxygenase 1, were higher in preeclamptic women as compared to normotensive pregnant women. Endoglin levels were significantly lower in cord blood of preeclamptic mother as compared to normotensive mothers. Serum and cord blood vitamin B12, Apo A-I and Apo B l, cholinesterase, leptin levels, IGF-I were lower in preeclamptic women as compared to normotensive pregnant. Conclusion: Findings of the present study suggest that biochemical alterations occur in mothers and fetuses and modifications of uterine environment (in terms of thyroxine and folate and vitamin B12 supplementation) can be of help.
Keywords: preeclampsia